HYDRONEPHROSIS MIMICKING OVARIAN CYST - Begum, Nazakat; Mohammad, Gul; Ahmed, Rashid (Journal of Ayub Medical College Abbottabad, 1988)
Unilateral hydronephrosis is usually caused by obstruction at the pelviureteric junction or in the ureter caused by various aetiological factors. Most of the time it is symptomatic and confirmed on radiology. But at time hydronephrosis is painless and asymptomatic and presents itself as a mass. If it attains a large size the vessels become elongated and if due to repeated pregnancies the abdominal muscles become lax, then kidney may be pushed down and present as a lower abdominal mass. Here we record a case of giant hydronephrosis which presented as a lower abdominal mass and was confirmed on laparotomy